2006
DOI: 10.1677/erc.1.01230
|View full text |Cite
|
Sign up to set email alerts
|

Selective spatial upregulation of intratumoral stromal aromatase in breast cancer patients: evidence for imbalance of local estrogen metabolism

Abstract: The suppression of local estrogens levels is of key importance in the treatment of ER-positive breast cancer. Essentially all endocrine strategies act by either suppressing estrogen formation or competitively inhibiting receptor-binding in tumor cells. Nevertheless, little is still known about the local expression of aromatase and sulfotransferase which are the key modulators of intra-tumoral estrogen levels. We have performed immunohistochemostry to investigate the expression of aromatase and sulfotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…This hypothesis is partly supported by our observation that ER-positive patients with tumours coexpressing PgR had prolonged RFS compared to those lacking PgR, because PgR is induced by oestrogens at the transcriptional level and is recognised to be associated with a better prognosis and treatment response. When using immunohistochemistry on tumour specimen's aromatase expression was found both in the stroma and in tumour epithelial cells, which is in agreement with what others have seen [29,[38][39][40][41][42]. Interestingly, we found that protein expression of stromal but not cancer epithelial aromatase was related to breast cancer prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…This hypothesis is partly supported by our observation that ER-positive patients with tumours coexpressing PgR had prolonged RFS compared to those lacking PgR, because PgR is induced by oestrogens at the transcriptional level and is recognised to be associated with a better prognosis and treatment response. When using immunohistochemistry on tumour specimen's aromatase expression was found both in the stroma and in tumour epithelial cells, which is in agreement with what others have seen [29,[38][39][40][41][42]. Interestingly, we found that protein expression of stromal but not cancer epithelial aromatase was related to breast cancer prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding tumors, the presence of aromatase has already been described in breast cancer cells, 1,25,26 as well as in endometrial, 2,27 uterine cervix, 28 ovarian, 3 prolactinsecreting and plurihormonal pituitary adenomas, 29 and in non-small cell lung cancer. 30 Similar to our statement on normal meninges, to date, there are no data in the literature on aromatase expression in meningiomas, which demonstrated negative in the present series.…”
Section: Discussionmentioning
confidence: 96%
“…The anti-aromatase antibody (dilution 1:1,000 in PBS/Tween) was generated from a rabbit immunoglobin fraction of an antiserum prepared against human placental aromatase and was kindly provided and validated by Dr N Harada (Fujita Health University Hospital, Toyaoake, Japan) (Sasano et al 1994(Sasano et al , 1996. The monoclonal mouse EST Ab1 antibody (EST.1) was purchased from NeoMarkers (Fremont, CA, USA) and was used at a concentration of 2 g/ml with subsequent boiling of tissue sections in 10 mM citrate buVer at pH 6.0 for 15 min as previously described (Singer et al 2006). All slides were incubated overnight at 4°C, followed by a PBS wash for 5 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%